Measurements of Serum Pituitary-Gonadal Hormones and Investigation of Sexual and Reproductive Functions in Kidney Transplant Recipients - Guang-chun Wang; Jun-hua Zheng; Long-gen Xu; Zhi-lian Min; You-hua Zhu; Jun Qi; Qiang-lin Duan (International Journal of Nephrology)
Objective. To investigate changes in serum pituitary-gonadal hormones and restoration of sexual and reproductive functions after successful kidney transplantation. Patients and Methods. Serum pituitary-gonadal hormones before and after kidney transplantation were measured in 78 patients with end-stage renal disease (ESRD) and in 30 healthy adults. Pre- and postoperative semen specimens of 46 male recipients and 15 male controls were collected and compared. Additional 100 married kidney transplant recipients without children were followed up for 3 years to observe their sexual function and fertility. Results. Serum PRL, LH, and T or E2 levels gradually restored to the normal ranges in all kidney transplant recipients, and sperm density, motility, viability, and morphology significantly improved in the male recipients 4 months after successful kidney transplantation (P<.05). Thirty-three male recipients (55.93%) reobtained normal erectile function, and 49 kidney transplant recipients (61.25%) had children within the 3-year follow-up period. Conclusion. Successful kidney transplantation could effectively improve pituitary-gonadal hormone disturbance and sexual and reproductive dysfunctions of ESRD patients.